Determination of Toxicity of some Fungal Metabolites on Seed Germination and Pigment Leaching - M. Chavan, Rajendra B. Kakde* and Ashok (Journal of Ecobiotechnology, 2010)
<span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA; mso-bidi-font-family: 'Times New Roman';">In present investigation, eighteen fungi were isolated on Potato Dextrose Agar and Rose Bengal Agar medium from abnormal soybean seeds. Out of these eighteen fungi, ten dominant fungi were selected to study the toxic potentialities of culture filtrate of these ten fungi on oilseeds germination, pigment leaching i.e. chlorophyll of spinach and betalain of beet root. Maximum loss of chlorophylls was caused due to toxins of Aspergillus niger, Aspergillus flavus and Penicillium notatum. Fusarium oxysporum caused minimum loss of chlorophylls. Aspergillus niger and Alternaria dianthicola was responsible for maximum leaching of betalain pigment while Curvularia lunata causes minimum leaching of pigment. <span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA; mso-bidi-font-family: 'Times New Roman';">--- <span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA; mso-bidi-font-family: 'Times New Roman';"> Seed Pathology and Fungal Biotechnology Laboratory, Department of Botany, Dr. Babasaheb Ambedkar Marathwada University, Aurangabad- 431004(M.S.) India --- Please Cite This Article As: Rajendra B. Kakde and Ashok M. Chavan. 2010. Determination of Toxicity of some Fungal Metabolites on Seed Germination and Pigment Leaching. J. Ecobiotechnol. 2(6):46-55.